Implementasi Nilai-Nilai Pendidikan Agama Islam Multikultural Melalui Edu-Ekowisata: Studi kasus Paguyuban Paku Lima Dusun Mandaran Desa Pesisir Kecamatan Besuki Kabupaten Situbondo - Agus Sulthoni Imami Sulthon; Masykuri Bakri; Hambali Hambali (Muróbbî: Jurnal Ilmu Pendidikan, 2021)
Multicultural Islamic Education Paradigm is an Islamic teaching that emphasizes tolerance, harmony, moderation, and open dialogue in diversity. The reality of the pluralistic Indonesian nation requires a paradigm that can knit diversity. Multicultural Islamic Education is one means that can understand a diverse society about the importance of mutual understanding and cooperation in managing the sustainability of the coastal environment. In essence, beach tourism is also an instrument for scientific activities, beach tourism has an active role as an educational instrument and a playing media. This study aims to find the implementation of the values ??of Multicultural Islamic Religious Education through edu-ecotourism to support religious education, mediation of horizontal social conflicts. The implementation of these values ??is a strategy for developing the community Paku Lima in Mandaran Hamlet, Pesisir Village, Besuki District, Situbondo Regency. The type of research used is qualitative research with a qualitative approach that is applied using in-depth interviews and group depth interviews. Determination of informants was done by purposive sampling, the number of respondents was 20 people from the association committee and 10 people from the surrounding community. Data were analyzed and analyzed using an interactive model using the theory of Miles, Huberman, and Saldana, namely: (1) data condensation, (2) presentation of data, and (3) drawing conclusions. Based on the results and data analysis, it was concluded that the implementation of PAIM values ??through edu-ecotourism was effectively applied through the community association, especially considering the complexity of problems arising from ethnic diversity and interests between groups. The strategy of developing the association by combining PAIM-oriented education with edu-ecotourism makes the association a vehicle for harmony and also as a mediator in resolving the problem of horizontal conflicts between ethnic communities